Comment on Hajra et al.: “High-temperature phase stability and phase transformations of Niobium-Chromium Laves phase: Experimental and first-principles calculation” - Andreas Leineweber; Frank Stein (Materials & Design)
This work comments on a recent publication by Hajra et al. (Mater. Design 236 (2023) 112483), which claims to have presented compelling experimental and theoretical evidence in favour of the existence of an equilibrium C14-NbCr2 high-temperature Laves phase in the Cr-Nb system. In the present comment, evidence and conclusions reported in the paper of Hajra et al. are critically put into context of insight from previous works. From this it is concluded here, that the evidence in favour of an equilibrium C14-NbCr2 high-temperature Laves phase is, by far, not that compelling as claimed by Hajra et al.. Instead, the most direct evidence presented in the literature does not support the existence of an equilibrium C14-NbCr2 high-temperature Laves phase. Alternative interpretations of Hajra et al.’s evidence and conclusions are offered, and it is elaborated, which true gaps in knowledge exist concerning the Laves phases in the Cr-Nb system.